CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. GRAB INDONESIA DI ERA NEW NORMAL MASA PANDEMI COVID-19 - Novita Damayanti; Yuni Retna Dewi (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Today, the social responsibility of a company or better known as CSR has become the subject of discussion among the public and business people. PT. Grab Indonesia, as an Indonesian online transportation application, together with the government, carried out a covid 19 vaccination as an implementation of CSR in the New Normal era of the Covid-19 pandemic in several regions in Indonesia for the elderly and online transportation drivers. This study aims to determine the implementation of Grab Indonesia's